Game theory and strategy - Straffin, Philip D. (New mathematical library ;, 1993)
Game theory is the study of how people play games. What is the proper strategy to employ when the game situation is in constant flux and other players are forming different strategies? Since 1944, game theory has been applied to a variety of situations including economics, politics, philosophy, social psychology, and biology. This book serves as an introduction to game theory and requires no more math skills tha basic algebra.